Towards Inclusive Canal Water Management for Resilience Agri-food Systems in Coastal Bangladesh - Sarker, Mou Rani; Mannan, Fouzia; Rahman, M. Mokhlesur (2024)
Freshwater canals, traditionally open for communal use, play a vital role in food production and domestic needs. However, governing these canals as common-pool resources presents significant challenges. Conflicts over freshwater access often arise from resource appropriation and control by local elites, compounded by ambiguous policy interpretations. This unequal distribution of resources disproportionately impacts marginalized tenant farmers and women, whose livelihoods depend heavily on agri-food systems. Addressing these issues needs recognizing community diversity and the entrenched sociopolitical dynamics that shape resource governance. Although elite domination persists, encouraging efforts are emerging. Communities are increasingly mobilizing to resist illegal water capture, elevate marginalized voices, and enhance collective water management. These initiatives foster more sustainable and equitable development, with potential benefits extending both nationally and globally.